In vitro Antioxidant and Acetylcholinesterase Inhibitory Activities of the Sesquiterpenes of a Symbiotic Actinomycete Streptomyces sp. from South China Sea - Wen, Lu; Chen, Gang; Zhang, Shichang; You, Tinghuo; Liu, Fan; Fu, Yuhong; Yao, Xiangcao (Asian Journal of Chemistry, 2013)
Marine microorganism possesses special metabolic approach to produce compounds with new structures and significant activities. However, reports on secondary metabolites of the symbiotic microorganisms of stony corals are rarely reported up to date. In the course of our search for active constituents from the symbiotic microorganisms of stony corals from the south China sea, five sesquiterpenes were isolated from the actinomycete Streptomyces sp. (ZJG1) and their structures were elucidated by spectrometric methods (NMR, MS and IR, etc). The five sesquiterpenes were analyzed for possible antioxidant and acetylcholinesterase inhibitory activities in three testing systems, including DPPH scavenging method, hemolysis assay and acetylcholinesterase inhibition methods. Compound 3 showed good activities in three tests and compound 2 exhibited well free radical scavenging and acetylcholinesterase inhibitory activity.